Real-time searching of big data with Solr and Hadoop - Cope, Ron.; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa Clara, CA) ([United States?] : O'Reilly Media, 2011)
"Hadoop and HBase make it easy to store terabytes of data, but how do you scale your search mechanism to sift through these mountains of bits and retrieve large result sets in a matter of milliseconds? Careful use of the Solr search server, based on Lucene, made these requirements come to life in our production environment. Come learn how we query terabytes of data in a highly available system." --Resource description page.
Title from title screen.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, Calif.
Electronic reproduction.
Keywords: Electronic data processing; Data mining; Open source software; Electronic books